An Analysis on the Use of Code Mixing in Azka Corbuzier's Youtube Channel - Sugiarto, A.R; Nizam Ahsani (CV. Creative Tugu Pena, 2024)
This study aims to analyse code-mixing in Azka Corbuzier's YouTube videos, given the importance of language as a primary communication tool. Code-mixing, the combination of two languages within a single utterance, is intriguing to study in the context of using Indonesian and English simultaneously. Therefore, the main purpose of this study is to analyse the types of code mixing used by Azka Corbuzier's video YouTube channel and the factors that drive Azka Corbuzier to use code mixing in his utterances. This study collected data by watching and transcribing five episodes of Azka Corbuzier's video on the YouTube channel. Hoffman's theory of types of code-mixing, including intra-sentential, intralexical, and changes in pronunciation, guided the classification of the data. The results showed that intra-sentential code-mixing is the most common utterance, with 57 out of 60 total instances. We found three instances of intralexical code-mixing, but no instances of changes in pronunciation. Factors influencing Azka Corbuzier's use of code-mixing include habit, communication situations, topics, educational background, social prestige, language proficiency, and cultural influences. This study also concluded that Azka Corbuzier's videos, through code-mixing, reflect complex linguistic and social dynamics, where the use of two languages facilitates communication and expresses cultural identity.